Needs-based quality of life in adults dependent on home parenteral nutrition. Issue 3 (June 2019) - Burden, Sorrel T.; Jones, Debra J.; Gittins, Matthew; Ablett, Joanne; Taylor, Michael; Mountford, Christopher; Tyrrell-Price, Jonathan; Donnellan, Clare; Leslie, Fiona; Bowling, Tim; Gabe, Simon; Rahman, Farooq; et al.
Summary: Background & aims: Home parenteral nutrition (HPN) provides life sustaining treatment for people with chronic intestinal failure. Individuals may require HPN for months or years and are dependent on regular intravenous infusions, usually 12–14 h overnight between 1 and 7 days each week. This regime can have adverse impact on the life of people dependent on the treatment. The aim of this study was to establish mean values for the Parenteral Nutrition Impact Questionnaire (PNIQ) and to determine the effect of disease, frequency of infusions per week and patient characteristics on quality of life of patients fed HPN. Method: The PNIQ was distributed to patients across nine UK HPN clinics. Data were analysed using linear regression, with PNIQ score as the dependent variable and potential confounders as independent variables. Unadjusted and adjusted models are presented. Higher PNIQ scores reflect poorer quality of life. Results: Completed questionnaires were received from 466 people dependent on HPN. Mean PNIQ score was 11.04 (SD 5.79). A higher PNIQ score (effect size 0.52, CI 0.184 to 0.853) was recorded in those dependent on a higher frequency of HPN infusions per week. Respondents with cancer had a similar mean PNIQ score to those with inflammatory bowel disease (mean 10.82, SD 6.00 versus 11.04, SD 5.91). Those with surgical complications reported a poorer QoL (effect size 3.03, CI 0.642 to 5.418) and those with severe gastro-intestinal dysmotility reported a better QoL (effect size −3.03, CI −5.593 to −0.468), compared to other disease states. Conclusions: This large cohort study of quality of life in chronic intestinal failure demonstrates that HPN impacts individuals differently depending on their underlying disease. Furthermore, since the number of HPN infusions required per week is inversely related to an individual's needs-based quality of life, therapies that reduce PN burden should lead to an improvement in QoL. Highlights: Study of quality of life in 466 individuals on Parenteral Nutrition infusions. Parenteral Nutrition Impact Questionnaire gauges quality of life in those on infusions. Patients requiring more frequent infusions per week reported poorer quality of life. Parental nutrition impacts differently on people depending on underlying disease.